Hakikat Perceraian Berdasarkan Ketentuan Hukum Islam Di Indonesia - Dahwadin Dahwadin; Enceng Iip Syaripudin; Eva Sofiawati; Muhamad Dani Somantri (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2020)
Divorce is one of the provisions contained inside constitution number 7 years 1989 article 65 about religious justice and compilation of islamic law article 115 and constitution number 1 years 1974 about marriage article 39 explain that divorce only can be done in front of the trial religious court after religious court trying and not succeeding reconcile the two sides. The main purpose divorce to be affairs authority religious court (see article 49) is to give discipline de jure for people who are Muslim in handling family matters. So that with various presence which mandates divorce done in front of the trial give taste satisfaction and comfort for seekers justice in search justice on environment of the religious court. Theory in writing this is used as basic analysis write in reviewing normatively and scientific  that is legal purpose theory, legal development, law enforcement and law enforcement in Indonesia. Normatively study write used legal basis which applies in the environment religious court in Indonesia. Between : 1) constitution number 1 years 1974 about is marriage. Constitusion number 7 years 1989. Constitution number 3 years 2006 Jo constitution number 50 years 2009 about is religious court, compilation of islamic law, and PP number 9 years 1975 about is implementation constitution number 1 years 1974 with the purpose of creating justice, benefit, discipline and peace of the community, and benefit for people who seek justice in the environment religious court in Indonesia. AbstrakPerceraian merupakan salah satu ketentuan yang terdapat di dalam Undang-undang No 7 Tahun 1989 Pasal 65 tentang Peradilan Agama dan Kompilasi Hukum Islam (KHI) Pasal 115 dan UU No. 1 Tahun 1974 tentang Perkawinan Pasal 39 menjelaskan bahwasannya perceraian hanya dapat dilakukan di depan sidang Pengadilan Agama setelah Pengadilan Agama  berusaha dan tidak berhasil mendamaikan kedua belah pihak. Tujuan utama perceraian menjadi urusan wewenang pengadilan agama (lihat Ps. 49) adalah untuk memberikan ketertiban secara hukum bagi orang-orang yang beragama Islam dalam menangani persoalan keluarga. Sehingga dengan hadirnya berbagai ketentuan yang mengamanatkan perceraian di lakukan di depan sidang pengadilan memberikan rasa kepuasan dan kenyamanan bagi para pencari keadilan dalam mencari keadilan di lingkungan badan peradilan agama. Teori dalam penulisan ini yang digunakan sebagai dasar analisis penulis dalam mengkaji secara normative dan ilmiah yaitu teori tujuan hukum, pembangunan hukum, penegkan hukum dan pemberlakuan hukum di Indonesia. Kajian secara normatif penulis menggunakan dasar hukum yang berlaku di lingkungan lembaga pengadilan agama di Indonesia. Diantaranya : 1) UU No. 1 Tahun 1974 tentang Perkawinan. UU No. 7 Tahun 1989 Jo UU No. 3 Tahun 2006 Jo UU No. 50 Tahun 2009 tentang Peradilan Agama, Kompilasi Hukum Islam (KHI), dan PP No. 9 Tahun 1975 tentang Pelaksanaan UU No. 1 Tahun 1974 dengan tujuan untuk menciptakan keadilan, kemanfaatan, ketertiban dan ketentraman masyarakat, dan kemaslahatan bagi orang-orang yang mencari keadilan di lingkungan badan peradilan agama di Indonesia.